0
$\begingroup$

Let $X$ be a r.v. with pdf $f(x)$ and let $F(x)$ be the distribution function.

Let $r(x)=\dfrac{x.f(x)}{(1-F(x))}$, Then for $x< e^u$ and $f(x)=\dfrac{e^{-\dfrac{(\log x-\mu)^2}{2}}}{x\sqrt{2\pi}}$ , the function $r(x)$ is

  • Increasing in $x$
  • Decreasing in $x$
  • Constant
  • None of the above

I basically first noted that $X$ has the lognormal distribution with parameter $\mu$ and $\sigma ^2=1$ and since $f(x)$ is continuosly differentiable in its domain, So I first figured out the mode of $X$ i.e. $x^* \in (0,\infty)$ that maximizes $f$ and in order to that I transformed $f$ to $\ln ({f})$ as its an increasing monotonnic tranformation.

This gave me $x^*=e^{\mu -1}$ and

  • for $x<x^*$, $f(x)$ is increasing i.e. $f'(x)>0 $
  • for $x>x^*$, $f(x)$ is decreasing i.e. $f'(x)<0 $

Then I finally differentiated $r(x)$ i.e.

$\begin{align*} r'(x) &= \dfrac{\overset{(1)}{\left (1-F(x)\right )}\overset{(2)}{\left (f(x)+xf'(x) \right )}+\overset{(3)}{x\left (f(x) \right )^2}}{\left ( 1-F(x) \right )^2}\\ \end{align*}$

  1. (1) is always positive as $\begin{matrix} F(x) < 1 & \forall x \in (0, \infty) \end{matrix}$
  2. (2) is positive for $x \le e^{\mu -1}$ but for $x \in (e^{\mu -1}, e^{\mu})$ we can't say anything
  3. (3) is always positive

    Therefore for $x\in (0,e^{\mu -1})$ $r(x)$ is increasing but for $x \in (e^{\mu -1}, e^{\mu})$ we can't say anything about $r(x)$. Therefore, for $x< e^u$ we can't say anything definite about $r(x)$ and none of the three options given are correct.

But as per answer key first option is correct i.e. $r(x)$ is increasing.

I don't know where I am going wrong.

$\endgroup$

1 Answer 1

0
$\begingroup$

If $X \sim \operatorname{LogNormal}(\mu,1)$, then $Y = \log X \sim \operatorname{Normal}(\mu,1)$. Consequently, $$f_X(x) = \frac{1}{x} f_Y(\log x),$$ and $$F_X(x) = \Pr[X \le x] = \Pr[\log X \le \log x] = \Pr[Y \le \log x] = F_Y(\log x).$$ It follows that $$r(x) = \frac{x f_X(x)}{1 - F_X(x)} = \frac{f_Y(\log x)}{1 - F_Y(\log x)} = \frac{f_Y(y)}{1 - F_Y(y)},$$ where $f_Y$ and $F_Y$ are the density and CDF of a normal distribution with mean $\mu$ and variance $1$. But this means that $r(e^x) = \lambda_Y(y)$; i.e. $r(e^x)$ is the hazard function of such a normal distribution.

Since $Y = Z + \mu$ for a standard normal variable $Z$, the hazard function of $Y$ is invariant with respect to the location parameter, so it suffices to consider the hazard of $Z$ (i.e., $\lambda_Y(y) = \lambda_Z(y - \mu)$). So all that remains is to look at $$\begin{align*} \frac{d}{dz}\left[\frac{e^{-z^2/2}}{1 - \Phi(z)}\right] &= \frac{(1-\Phi(z))(-z)e^{-z^2/2} - e^{-z^2/2}(-e^{-z^2/2}/\sqrt{2\pi})}{(1-\Phi(z))^2} \\ &= \frac{e^{-z^2/2}}{(1-\Phi(z))^2} \left( \frac{e^{-z^2/2}}{\sqrt{2\pi}} - z(1 - \Phi(z)) \right)\end{align*}.$$ For $z < 0$, the term in parentheses is obviously positive; thus for $Y < \mu$, or equivalently, $X < e^{\mu}$, the hazard function is increasing.

In fact, $r$ is increasing for all $X$, not just for the given restriction.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.